Performance of Livestock Marketing in Indonesia: A Sociological Analyst of Livestock Traders - ., Syahyuti (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
The problem face by livestock agribusiness system is inefficiency marketing subsystem performance and there is weakness integrated of the others subsystem especially the production subsystem. Research on livestock marketing in Indonesia is usually limited on the economic view that is narrow coverage . This paper discusses social system aspect of livestock traders who conduct livestock marketing by applying procedure which on exclusive value system in the market economy system that is characterized by informal and traditional systems. Data of this study are secondary which include behavior of the traders. Traders face dilemma in conducting their activities as the brokers between different norm of rural and urban communities. There are ambivalent attitude ofthe livestock traders those are positive side as the agribusiness catalyst and the negative side are regarded as the source of inefficiency and unfairness of agribusiness system. Efficiently subsystem of marketing will encourage new technology implementation in the production subsystem indirectly. Set of agribusiness system should ensure fairness among the marketing actors to achieve sustainable system through understanding of traders roles more proportionally Key words: Livestock, livestock marketing, livestock traders